Prevalence of sudden unexpected death of infants and its subcategories in low- or middle-income countries: a systematic review protocol - Liesl Zühlke; David Coetzee; Mark Engel; Natasha R Rhoda; Eunice Turawa; Imen Ayouni; Shanaaz Mathews (BMJ Open)
Introduction Infant mortality in low or middle-income countries (LoMICs) is still triple that of high-income countries (HICs), and the high mortality burden regions are also weighed down by a triple or quadruple burden of disease such as HIV and tuberculosis; chronic illness; mental health; injury and violence; and maternal, neonatal and child mortality. Emerging data suggest that the sudden unexpected death in infancy (SUDI) burden in LoMICs is at least 10-fold that in HICs. While ending preventable deaths in the neonatal period has received some global attention, the postnatal period where SUDIs occur is a poorly understood and data-poor area in LoMICs. We propose conducting a systematic review to evaluate the burden and trends of SUDIs in LoMICs since 2004.Methods and analysis We will systematically search PubMed, Web of Science, Scopus, African Index Medicus, EBSCOHost, Google Scholar, WHOIS and WHO database to identify studies published from July 2004 until October 2024. Two reviewers will screen titles and abstracts and select full-text articles independently for review. We will use the tool developed by the South African Medical Research Council—Burden of Disease Review Manager (BODRevMan)—to assess the risk of bias for each included study. Risk of bias will be assessed for each included study. Information on the prevalence and/or incidence of SUDI and its subcategories and case definitions will be extracted from each article. Where possible, data on prevalence, incidence and subcategories will be pooled using a random effects meta-analysis to account for variability between estimates. The I2 statistic will establish the level of heterogeneity due to variation in estimates rather than chance. Results will be presented in tables and graphs. The systematic review will be reported according to the PRISMA 2020 checklist.Ethics and dissemination Ethical approval is not required as this is a protocol for a systematic review. Findings will be disseminated through peer-reviewed publications and conference presentations.PROSPERO registration number CRD42023466162.